Machine-based production scheduling for rotomoulded plastics manufacturing. Issue 5 (4th March 2021) - Baxendale, Mark; McGree, James M.; Bellette, Aaron; Corry, Paul
Abstract : In this paper, production scheduling for rotomoulded plastics manufacturing in a multi-machine environment is considered. The objective is to minimise total tardiness. The problem has some commonality with hybrid flow shop scheduling with batching, where additional constraints are needed to control which machines may be used at each stage. The problem is shown to be NP-hard and is formulated as a mixed integer program. Given consequently large solve times to obtain optimal solutions, simulated annealing and tabu search algorithms were developed alongside a constructive heuristic to obtain near-optimal solutions within a practical time-frame. The solution algorithms were tuned and tested using randomly generated problem instances. The best results in terms of solution quality were generally obtained by simulated annealing. The problem instances were generated to be representative of a real production environment located in Queensland, Australia.